QSAR and docking studies of pyrazole analogs as antiproliferative against human colorectal adenocarcinoma cell line HT-29 - Mohamed, Hiba Hashim Mahgoub; Hussien, Amna Bint Wahab Elrashid Mohammed; Saeed, Ahmed Elsadig Mohammed (European Journal of Chemistry, 2022)
In-silico quantitative structure-activity relationship (QSAR) study was performed to develop a model on a series of novel pyrazole derivatives containing acetamide moiety which exhibited considerable antiproliferative activity against human colorectal adenocarcinoma cell line HT-29. The model obtained has a correlation coefficient (r) of 0.9693, squared correlation coefficient (r2) of 0.9395 and a leave-one-out (LOO) cross-validation coefficient (Q2) value of 0.8744. The predictive power of the developed model was confirmed by the external validation which has an r2 value of 0.9488. These parameters confirm the stability and robustness of the model to predict the activity of a new designed set of 3,5-dimethyl-pyrazole derivatives (22-36), results indicated that the compounds 26, 31, 35, and 36 showed the strongest antiproliferative activity with (IC50 = 0.182, 0.172, 0.166 and 0.024 μM, respectively) against human colorectal adenocarcinoma cell line HT-29 compared to the reference vemurafenib with (IC50 = 1.52 μM). Molecular docking was performed on the new designed compounds with the human colorectal adenocarcinoma cell line 5JRQ protein. The docking results showed that compounds 26, 31, 35, and 36 have docking affinity of -8.528, -5.932, 23.017 and 18.432 kcal/mol, respectively.